0042 Implementing innovative strategies to reduce distracted and impaired driving through a multi-state community of practice. (26th April 2015) - Hunt, Rebekah
Abstract : Statement of purpose: In 2012, 10, 322 people lost their lives in crashes in which a driver was impaired, accounting for 31% of all traffic fatalities in the US (NHTSA, Traffic Safety Facts 2012, pg. 110). In the same year, an additional 3, 328 people lost their lives and an estimated 421, 000 were injured in crashes in which a driver was distracted (distraction.gov ). The Children's Safety Network's (CSN) Community of Practice (CoP) on the prevention of distracted and impaired driving provides a sustained forum in which states learn about and implement evidence-based strategies for reducing these injuries. Methods/Approach: In October 2014, CSN launched this new CoP with participation by ten states. The CoP promotes peer-to-peer sharing and networking and offers monthly webinars featuring presentations by experts. Since it started, the CoP has explored data sources, data collection, and teen engagement in distracted and impaired driving prevention. The group has also shared the goals each state team has set for itself. In coming months, the CoP will look at applying the lessons learned from preventing alcohol-impaired driving to preventing marijuana-impaired driving; engaging parents; avoiding non-evidence based programs; and distraction caused by using handheld devices while driving. Results: The ten participating states have formed state-specific teams consisting of Departments of Public Health, Transportation and Highway Safety, Emergency Medical Services for Children, Brain Injury Alliances and Associations, Offices of Public Instruction, Offices of Public Safety and Highway Patrol, foundations, coalitions and task forces, AAA, insurance companies and others. They are implementing a wide variety of innovative strategies for addressing distracted and impaired driving, including landscape assessments; peer-to-peer trainings; social norms change campaigns; and toolkit development. Conclusions: The CoP members continually learn from one another. One team recently discovered an ally in local media, where a journalist tracks and consolidates legislative changes and interventions for preventing distracted driving. That team encouraged others to explore local media in their state for similar resources. Another team sought feedback on administering and boosting response rates for a statewide survey. Still others have been inspired to invite new stakeholders to their teams, explore the data on previously unknown problems-such as distraction from hands free devices, or prescription drug impairment-and evaluate changes in behaviour using other teams' evaluation tools and strategies. Significance and contribution to the field: The CoP provides a space for agencies to come together within states, and across state lines. It opens new channels of communication for generating innovative ideas, and learning important lessons from others who have "been there before." It is a platform for developing collective and coordinated action-from data collection, to public messaging, program implementation, and enforcement-that can more efficiently reduce the burden of distracted and impaired driving. Using state specific examples, this presentation will cover information about the distracted and impaired driving burdeb, the teams' priority topic areas and goals, and the key lessons learned through the CoP to date.